Analisis Sistem Pembelajaran Full Day School pada Implementasi Kurikulum Merdeka di Kelas IV SD Luqman Al Hakim Ngawi Tahun Pelajaran 2022/2023 - Hidayah, Nurul; Nur’afifah, Uci Ulfa; Dimas, Arifian (Global Education Journal, 2023)
This research aims to determine the full day school learning system in the implementation of their curriculum in class IV of SD Luqman Al Hakim Ngawi. The implementation of the full day school learning system at SD Luqman Al Hakim Ngawi was carried out starting from the school's inception. Learning is carried out from 07.00 to 16.00 and is carried out quite well. The method used in this research is qualitative research. The data collection technique used is compiling all data obtained from observation, interviews, and documentation. Data validity techniques are carried out using trustworthiness, dependability. and confirmability. And data analysis in this research consists of data collection, data condensation, data presentation, and drawing conclusions. The results of the research show that the full day school learning system in the implementation of the independent curriculum at SD Luqman Al Hakim has been implemented since the founding of the school, and currently implements two curricula, namely the government curriculum and the typical Hidayatullah Islamic boarding school curriculum, but in the end the school prioritizes its own curriculum in the form of a typical curriculum. Islamic boarding schools that prioritize students' religious character and Al-Qur'an education.